Dimerization of P-Selectin Glycoprotein Ligand-1 (PSGL-1) Required for Optimal Recognition of P-Selectin - Snapp, Karen R. (The Rockefeller University Press, 1998)
Interactions between P-selectin, expressed on endothelial cells and activated platelets, and its leukocyte ligand, a homodimer termed P-selectin glycoprotein ligand-1 (PSGL-1), mediate the earliest adhesive events during an inflammatory response. To investigate whether dimerization of PSGL-1 is essential for functional interactions with P-selectin, a mutant form of PSGL-1 was generated in which the conserved membrane proximal cysteine was mutated to alanine (designated C320A). Western blotting under both denaturing and native conditions of the C320A PSGL-1 mutant isolated from stably transfected cells revealed expression of only a monomeric form of PSGL-1. In contrast to cells cotransfected with α1-3 fucosyltransferase-VII (FucT-VII) plus PSGL-1, K562 cells expressing FucT-VII plus C320A failed to bind COS cells transfected with P-selectin in a low shear adhesion assay, or to roll on CHO cells transfected with P-selectin under conditions of physiologic flow. In addition, C320A transfectants failed to bind chimeric P-selectin fusion proteins. Both PSGL-1 and C320A were uniformly distributed on the surface of transfected K562 cells. Thus, dimerization of PSGL-1 through the single, conserved, extracellular cysteine is essential for functional recognition of P-selectin.